Tax competition, environmental regulation and high-quality economic development: An empirical test based on spatial Durbin model - Shangguan, Xuming; Hashmi, Shabir Mohsin; Hu, Haiya; Wong, Wing-Keung (Frontiers in Public Health, 2022)
China's economy is moving towards high-quality development, and local governments face the dilemma of environmental governance and economic development. Based on the data from 278 prefecture-level and above cities from 2007 to 2017 in China, this paper assesses the impact of tax competition and environmental regulation on high-quality economic development by applying the spatial Durbin model and using instrumental variables. The paper finds that tax competition inhibits high-quality economic development and a positive spatial spillover effect. Environmental regulation has a significant direct promoting effect on high-quality economic development and a negative spatial spillover effect. Local government tax competition inhibits the promotion effect of environmental regulation on high-quality economic development. Further heterogeneity analysis shows that the direct and spatial spillover effects of tax competition and environmental regulation on high-quality economic development in large and medium-sized cities are significantly lower than those in small cities. Since the 18th National Congress of the Communist Party of China (CPC), the promotion effect of environmental regulation on high-quality economic development and the synergistic effect with tax competition has become more and more significant.